People perception on service quality towards both international and domestic hotel chain in China - jiang, limei (2009)
This work aims to assess the different demographic people’s perception on service quality in China's hotel chains, and effort to investigate how their perceptions affect potential purchase decisions, while comparing with management perception demonstrate the service gap between each party.